Desain Tes Diagnostik Three-Tier Multiple Choice dalam Mendeteksi Miskonsepsi Hidrolisis Garam - Pandu Jati Laksono; Deska Haliza; Mardiah Astuti (Al-TA'DIB: Jurnal Kajian Ilmu Kependidikan, 2021)
This study aims to determine the process of designing a three-tier multiple choice diagnostic test in detecting salt hydrolysis misconceptions and to determine students’ responses to the diagnostic test design has been developed. This research and development study involved students at one Islamic high school in Palembang and five validators. Data were gathered through validation sheets, questionnaires, interviews, and tests. The results showed that the three-tier multiple choice diagnostic test design on the developed salt hydrolysis material was declared valid and meeting the criteria for good items. The students responded positively to the design of the diagnostic test. Applications to larger data sources can be carried out further by adjusting the time in solving problems.Keywords: Chemistry; misconception; salt hydrolysis; three-tier multiple choice diagnostic test